A novel label-free fluorescent molecular beacon for the detection of 3′–5′ exonuclease enzymatic activity using DNA-templated copper nanoclusters. (10th August 2017) - Ge, Jia; Dong, Zhen-Zhen; Bai, Dong-Mei; Zhang, Lin; Hu, Ya-Lei; Ji, Dan-Yang; Li, Zhao-Hui
Abstract : A label-free biosensor was developed for highly sensitive and selective determination of Exo III based on poly(T) molecular beacon-templated CuNPs. Abstract : The 3′–5′ exonuclease plays key roles in maintaining genome stability; therefore, the detection of 3′–5′ exonuclease activity is very important for disease diagnosis and drug development. In this study, we present a novel highly sensitive and label-free fluorescent assay to detect the activity of exonuclease III (Exo III) using molecular beacon DNA with a polythymine (T) loop as a template for the formation of fluorescent copper nanoparticles (CuNPs). Upon the addition of Exo III, the molecular beacon probe was digested into mono- or short oligonucleotides by the exonucleases and failed to form fluorescent CuNPs. As a result, the fluorescence intensity of CuNPs decreased. This method exhibited a very low detection limit of 0.02 U mL −1 for Exo III. The designed molecular beacon probe can be a potential label-free strategy for the detection of other nuclease activity.